Microbiome Resilience and Health Implications for People in Half-Year Travel - Cheng, Mingyue; Liu, Hong; Han, Maozhen; Li, Shuai Cheng; Bu, Dongbo; Sun, Shiwei; Hu, Zhiqiang; Yang, Pengshuo; Wang, Rui; Liu, Yawen; Chen, Feng; Peng, Jianjun; et al. (Frontiers in Immunology, 2022)
Travel entail change in geography and diet, both of which are known as determinant factors in shaping the human gut microbiome. Additionally, altered gut microbiome modulates immunity, bringing about health implications in humans. To explore the effects of the mid-term travel on the gut microbiome, we generated 16S rRNA gene and metagenomic sequencing data from longitudinal samples collected over six months. We monitored dynamic trajectories of the gut microbiome variation of a Chinese volunteer team (VT) in their whole journey to Trinidad and Tobago (TAT). We found gut microbiome resilience that VT’s gut microbial compositions gradually transformed to the local TAT’s enterotypes during their six-month stay in TAT, and then reverted to their original enterotypes after VT’s return to Beijing in one month. Moreover, we identified driven species in this bi-directional plasticity that could play a role in immunity modulation, as exemplified by Bacteroides dorei that attenuated atherosclerotic lesion formation and effectively suppressed proinflammatory immune response. Another driven species P. copri could play a crucial role in rheumatoid arthritis pathogenesis, a chronic autoimmune disease. Carbohydrate-active enzymes are often implicated in immune and host-pathogen interactions, of which glycoside hydrolases were found decreased but glycosyltransferases and carbohydrate esterases increased during the travel; these functions were then restored after VT’ returning to Beijing. Furthermore, we discovered these microbial changes and restoration were mediated by VT people’s dietary changes. These findings indicate that half-year travel leads to change in enterotype and functional patterns, exerting effects on human health. Microbial intervention by dietary guidance in half-year travel would be conducive to immunity modulation for maintaining health.